A Sulfated Cyanobacterial Polysaccharide Proven as a Strong Inhibitor of Human Complement Activity in an In Vitro Assay - Flamm, Daniela; Blaschek, Wolfgang (Planta Medica, 2014)
Cyanobacterial exopolysaccharides are a rich source of, so far, widely unexplored polysaccharides. One of these exopolysaccharides is a highly sulfated, linear polysaccharide from Synechocystis aquatilis containing the amino sugar N-acetyl-fucosamine. Some sulfated polysaccharides and glycosaminoglycans are known to be inhibitors of the human complement system, which is an important part of the innate immune system. Defects in this system or misregulation can cause serious diseases. Therefore, new compounds with complement inhibiting activity and simple test assays are of great interest. Exopolysaccharides from S. aquatilis (arabinofucans) were compared to those from Synechocystis pevalekii (complex heteropolysaccharides) and the well-known complement inhibitor heparin. Investigations were performed with a modified ELISA test system based on a commercially available test kit quantifying the membrane attack complex. Hereby the testing becomes more stable, robust, reproducible, easier to handle and, for the first time, the effect of exopolysaccharides and heparin on the lectin pathway could be tested. The exopolysaccharides from S. aquatilis could be shown to be a 30 times stronger inhibitor of the classical pathway of the complement system compared to heparin (IC50 = 0.3 µg/mL vs. 9.2 µg/mL). These exopolysaccharides are also inhibitors of the lectin pathway (IC50 = 10.8 µg/mL) in which, however, heparin is more potent (IC50 = 2.0 µg/mL). Interestingly, these exopolysaccharides do not inhibit the alternative pathway. The exopolysaccharides from S. pevalekii are inactive in all pathways. Furthermore, partially hydrolyzed and desulfated exopolysaccharides from S. aquatilis were tested showing that a minimum molecular size and degree of sulfation are important for the inhibitory effects, whereas unspecific influences by complex formation of exopolysaccharides with calcium could be excluded.
Keywords: cyanobacteria; Synechocystis aquatilis; Synechocystis pevalekii; Merismopediaceae; Chroococcales; exopolysaccharides; sulfated arabinofucan; inhibition of human complement system